إستراتجة تقديم القصة لترقية مهارة الكلام في المعهد السلفي حملة القرءان جوكوراطا جومبانج : research on storytelling strategies in improving Arabic speaking skills at the Salafiyah Hamalatul Qur’an Islamic boarding school. (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Speaking skill is one of the language skills taught to students in learning the Arabic language. Speech is the main tool for building understanding and communication through the means of language. This speech activity is what stimulates the linguistics class, but it is often the opposite. The process of speech does not stimulate the situation and then finally stagnates. This causes students to be weak in mastering vocabulary and beautiful patterns.The method of this research is qualitative research with a qualitative descriptive approach, data obtained through observation, interview, and documentation, so that the data collected is in the form of information that is analyzed through data reduction, data analysis, and drawing conclusions. The results of this research can be summarized as follows: (1) The teaching step is to present the story Telling using the teacher’s direct method in order to enable the students to understand and master the Arabic language to the fullest extent, especially with regard to speaking skills. The goal is for students to master the material provided, including: choose an appropriate story, understand story structure, practice pronunciation and intonation, practice speaking, discuss the story, role-play and entertain, and create their own stories.(2) The Learning strategy of presenting the story is a powerful tool to improve the learning of students of the Boarding School Salafiyah “Hamalatul Qur’an” Jogoroto Jombang for the following reasons: emotional engagement, increased understanding, development of speaking and listening skills, strengthening moral values, stimulating creativity, richer use of language, and thus strengthening cultural connections. Story presentation can be an effective tool to enhance the learning experiences of students at various levels of education.